Elimination of Non-cytopathic Bovine Viral Diarrhea Virus From the LFBK-αvβ6 Cell Line - Gray, Ashley R.; Wood, Britta A.; Henry, Elisabeth; King, Donald P.; Mioulet, Valérie (Frontiers in Veterinary Science, 2021)
The LFBK-alphavbeta6 cell line is highly sensitive for the isolation of foot-and-mouth disease virus (FMDV) and porcinophilic vesicular viruses. However, LFBK-alphavbeta6 cells are contaminated with a non-cytopathic bovine viral diarrhea virus (BVDV), which complicates handling procedures in areas where other cell lines are maintained, as well downstream use of viral isolates. In this study, we used an aromatic cationic compound (DB772) to treat LFBK-alphavbeta6 cells using an approach that has been previously used to eliminate persistent BVDV from fetal fibroblast cell lines. After three cell passages with 4 µM DB772, BVDV could no longer be detected in unclarified cell suspensions using a pan-pestivirus real-time RT-PCR assay, and remained undetectable after treatment was stopped (nine passages) for an additional 28 passages. The analytical sensitivity of the DB772-treated LFBK-alphavbeta6 cultures (renamed WRL-LFBK-alphavbeta6) to titrations of FMDV and other vesicular virus isolates was comparable to untreated LFBK-alphavbeta6 cells. These new BVDV-free cells can be handled without the risk of cross-contaminating other cells lines or reagents, and used for routine diagnostics, in vivo studies and/or preparation of new vaccine strains.